2017
DOI: 10.1002/path.4981
|View full text |Cite
|
Sign up to set email alerts
|

Significance of perivascular tumour cells defined by CD109 expression in progression of glioma

Abstract: In the progression of glioma, tumour cells often exploit the perivascular microenvironment to promote their survival and resistance to conventional therapies. Some of these cells are considered to be brain tumour stem cells (BTSCs); however, the molecular nature of perivascular tumour cells has not been specifically clarified because of the complexity of glioma. Here, we identified CD109, a glycosylphosphatidylinositol-anchored protein and regulator of multiple signalling pathways, as a critical regulator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 46 publications
2
53
0
Order By: Relevance
“…Further work will be required to understand the degree to which these various CSC markers identify discrete and/or overlapping populations. These authors have also identified an interesting tumour‐promoting interaction between CSCs and adjacent NSTCs . We now add this interaction to the set of relationships that develop within GBM tumours that serve to resist our standard therapeutic interventions.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Further work will be required to understand the degree to which these various CSC markers identify discrete and/or overlapping populations. These authors have also identified an interesting tumour‐promoting interaction between CSCs and adjacent NSTCs . We now add this interaction to the set of relationships that develop within GBM tumours that serve to resist our standard therapeutic interventions.…”
Section: Discussionmentioning
confidence: 88%
“…Shiraki et al conclude their study by describing a rare example of CSC and NSTC cooperative interaction by demonstrating that the conditioned medium from CD109 + CSCs induces proliferation of CD109 − NSTCs . This finding strongly suggests that the CSCs lining the vasculature of the brain signal outwardly to drive cell division within adjacent NSTC populations (Figure A ).…”
Section: The Landscape Of Tumour Cell Interactionsmentioning
confidence: 92%
See 2 more Smart Citations
“…We previously reported that CD109‐deficient mice exhibit epidermal hyperplasia in skin and osteopenia in bone, suggesting possible CD109‐related physiological functions in vivo. Although previous studies report CD109 expression in various malignant tumors and correlation with prognosis in patients harboring a malignant tumor, such as a glioblastoma or lung adenocarcinoma, its roles in human disease remain largely unknown. In this review, we describe our views and perspectives on the significance of CD109 in malignant tumors and provide a description of our recent studies showing the involvement of CD109 in skin and bone‐tissue homeostasis in CD109‐deficient mice.…”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 99%